A Study of Cost Comparison in Anti-Hypertensive Drugs between Jan Aushadhi’s Generic Drugs and Branded Drugs - Immaculate, J. Christy (Indian Journal of Pharmacy Practice)
Background: Considering the long-term nature of hypertension and its continuous treatment requirements, the high cost of branded antihypertensive drugs poses a significant challenge for low-and middle-income patients. Generic medications, known for their comparable effectiveness to branded counterparts at a more affordable price point, can significantly reduce the financial burden on patients. The aim of this study was to analyze the cost variation between Jan Aushadhi’s generic drugs and branded medications for antihypertensive therapy. Materials and Methods: Cost minimization analysis study was conducted over a three-month period, from August 2023 to October 2023. We include Anti-hypertensive drugs listed in the Jan Aushadhi drug list. Results: Our findings show that Jan Aushadhi’s generic drugs were less costly than average branded drug cost. Ramipril 5 mg shows maximum price variation of 696%, while Bisoprolol 5 mg shows minimum variation of 40.91%. Conclusion: Our study concluded that cost disparity between Jan Aushadhi generic drugs and branded drugs commonly used for hypertension treatment in India.
Keywords: Hypertension; Anti-hypertensive drugs; Generic drugs; Branded drugs; Jan Aushadhi’s generic drugs